2014
DOI: 10.2478/s11535-014-0322-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic production and antioxidant properties of some Macedonian medicinal plants

Abstract: Investigations have been made to study the production of phenolic compounds (total phenolics, flavonoids and phenylpropanoids) and total antioxidant capacity in 27 Macedonian traditional medicinal plants to improve its potential as a source of natural antioxidants. Antioxidant potential of plant extracts was analyzed by five different assays: cupric reducing antioxidant capacity (CUPRAC), phosphomolybdenum method (PM), reducing power (RP), 2,2-diphenyl-1-picrylhydrazyl (DPPH·) and 2,2′-azinobis(3-ethylbenzothi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 55 publications
9
44
3
1
Order By: Relevance
“…Hence there are multiple ways of measuring the antioxidant effect of a source to have complete understanding of the mechanism of action. Furthermore, an extract showing low antioxidant activity could not be labelled as a poor source of antioxidant, since an extract is composed of chemicals with different functional groups and polarities and may behave differently depending on the reaction mixture [50]. We used ethanol as well as water as extraction solvents to dismiss the possibility that some of the polyphenols are not extractable in water due to poor solubility [51].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence there are multiple ways of measuring the antioxidant effect of a source to have complete understanding of the mechanism of action. Furthermore, an extract showing low antioxidant activity could not be labelled as a poor source of antioxidant, since an extract is composed of chemicals with different functional groups and polarities and may behave differently depending on the reaction mixture [50]. We used ethanol as well as water as extraction solvents to dismiss the possibility that some of the polyphenols are not extractable in water due to poor solubility [51].…”
Section: Resultsmentioning
confidence: 99%
“…The CUPRAC assay is widely used for measurement of the antioxidant capacity of plant extracts, due to the requirements of standard equipment, as well as fast and reproducible results [50]. This assay is based on the measurement of the absorbance of a complex that results from the reaction of antioxidant with Cu 2+ -neocuproine reagent [52].…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with those reported by Shan et al (2005) who noticed higher antioxidant activity from oregano extracts (1.01 mmol trolox/g dw) compared with sage (0.52 mmol trolox/g dw), rosemary (0.38 mmol trolox/g dw) and sweet basil (0.30 mmol trolox/g dw) extracts. In addition, Tusevski et al (2014), also observed higher antioxidant activity in extract of Origanum vulgare (714.15 μmol trolox/g dw) than in lemon balm (406.03 μmol trolox/g dw).…”
Section: Antioxidant Capacitymentioning
confidence: 86%
“…Therefore, antioxidants are considered important because of their many health benefits. Plants such as vegetables, fruits, herbs, and spices contain a wide variety of free radical scavenging molecules, such as phenolic compounds, nitrogen compounds, vitamins, and terpenoids, which have high antioxidant activities [3,4]. In view of these potential health benefits, intensive research has been conducted on natural antioxidants derived from plants.…”
Section: Introductionmentioning
confidence: 99%